Bologna 프로세스 이후 독일 대학 평생교육 체제 동향과 시사점 - 박성희(Seonghie Park); 권양이(Yangyi Kwon) (평생학습사회, 2019)
독일 대학 평생교육은 모두의 대학 교육기회 보장을 목적으로 개인의 삶의 질 및 국가경쟁력 향상에 주력하고 있다. 연방교육부는 “대학 문호개방”에 입각하여 성인근로자에게 장학금을 지원함으로써 모두의 대학 교육기회를 보장하는 평생교육 체제를 구축하였다. 2009년 이후 주교육부 장관회는 “대학 문호개방”의 원칙하에 전략적으로 근로자 및 자녀양육기 여성에게 대학교육 기회를 제공하고, 학습자 요구에 기반을 둔 성인친화적 교육과정 개발을 통해 유연한 학습조직을 구축해 왔다. 2019년 우리나라 교육부도 ‘대학의 평생교육체제 지원사업’ 기본계획을 통해 4차 산업혁명의 도래와 평균수명 연장으로 성인학습자가 성인 친화적 학사체제하에서 선취업 후진학 및 자기 계발을 하도록 체제 개편을 도모하고 있다. 연구 문제는 Bologna 프로세스 이후 대학 평생교육의 재조직화를 통해 상생적으로 발전하는 독일 대학 평생교육 체제 고찰이며, 연구 목적은 우리나라 성인 친화적 대학 평생교육 체제 구축을 위한 시사점 제언에 있다. 연구 결과, 독일 대학 평생교육 체제의 특징은 근로자의 직업평생교육에 중점을 두고, 대학 중앙본부에서 총장의 책임하에 대학의 특성에 기반한 프로그램을 개발하고, 궁극적으로 대학 문호개방을 통해 모든 이의 교육기회를 보장한다는 점이다. 이에 기초하여 우리나라 대학 평생교육에 시사점을 제언하였다. The German university lifelong education, focuses on improving the quality of life and national competitiveness for the purpose of actualizing higher education for all. The Federal Ministry of Education announced “improving through education: opening the college door” and has been strengthening financial aid and institutionalization for many adults to study in college. Since 2009, the State Education Ministers finalized the “Principles of Opening Universities”, while the university lifelong education program provided university education opportunities for industrial workers, child-raising women. That is, learners centered program so called adult friendly academic system, which led to flexible learning system. We explored the lifelong education system of German universities which is evolving through the reorganization of university lifelong education since the Bologna process. As a result, the characteristic of the lifelong education system in German universities is that it focuses on the vocational lifelong education of adult workers while the president is responsible for developing their own unique programs for all. On the basis of this, possible suggestions for the ﻿lifelong education system in Korean universities are discussed. KCI Citation Count: 8